2016
DOI: 10.1371/journal.pone.0163255
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Citrus-Associated Alternaria Species in Mediterranean Areas

Abstract: Alternaria brown spot is one of the most important diseases of tangerines and their hybrids worldwide. Recently, outbreaks in Mediterranean areas related to susceptible cultivars, refocused attention on the disease. Twenty representatives were selected from a collection of 180 isolates of Alternaria spp. from citrus leaves and fruit. They were characterized along with reference strains of Alternaria spp. Micro- and macroscopic characteristics separated most Alternaria isolates into six morphotypes referable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 50 publications
(62 reference statements)
4
38
1
Order By: Relevance
“…were not taken into consideration. Moreover, the variability of endopolygalacturonase gene has been reported to not be sufficient to discriminate accurately the different morphotypes . Indeed, authors identified a lower number of discriminating SNPs as compared to the present investigation.…”
Section: Discussioncontrasting
confidence: 71%
See 4 more Smart Citations
“…were not taken into consideration. Moreover, the variability of endopolygalacturonase gene has been reported to not be sufficient to discriminate accurately the different morphotypes . Indeed, authors identified a lower number of discriminating SNPs as compared to the present investigation.…”
Section: Discussioncontrasting
confidence: 71%
“…Concerning the first one, several genetic regions with higher sequence variation, compared to more classical barcoding regions such as ITS or endopolygalacturonase, were identified in Alternaria genus, and used to estimate phylogenies among small‐spored species . In particular, the SCAR marker OPA1–3 proved to be highly efficient in generating discriminant sequences . In the present study, the alignment of the OPA1–3 sequences, belonging to Alternaria reference strains of the species/morphotypes, more commonly reported on citrus, showed evidence of a high degree of variability.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations